Pengaruh Penerapan Model Team Games Tournament pada Materi Keanekaragaman Hayati Berbasis Games QuizWhizzer terhadap Motivasi dan Hasil Belajar pada Siswa/i Kelas VII - Sari, Octaviani; Turista, Dora Dayu Rahma; Maasawet, Elsje Theodora; Masitah, Masitah; Herliani, Herliani; Rambitan, Vandalita Maria Magdalena (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the effect of the application of the Team Games Tournament (TGT) model on biodiversity materials based on QuizWhizzer game media on the motivation and learning outcomes of grade VII students of SMP Negeri 7 Samarinda. The research method used was a quasi-experimental with a pretest-posttest control group design. The research subjects consisted of 25 students in grades VII-D as an experimental class using the QuizWhizzer-based TGT model, and 25 students in class VII-F as a control class using the discovery learning model. The results of the study showed that there was a significant influence of the application of the QuizWhizzer-based TGT model on student motivation and learning outcomes. Based on the results of the t-test, a significance value (2-tailed) of 0.001 < 0.05 was obtained which showed a significant influence on learning outcomes. The results of the N-Gain test showed an increase in learning outcomes in the medium category, with an average increase in the experimental class of 0.43, while the control class was 0.35. In addition, the results of the Mann-Whitney test on learning motivation showed a p-value of 0.000 < 0.05 which means that there is a significant difference between the two classes. Thus, it can be concluded that the use of the Team Games Tournament (TGT) model based on QuizWhizzer media has a significant effect on increasing student motivation and learning outcomes. This model has also been proven to increase students' interest in the learning process through fun game elements.